The essence of state policy of providing informational security as to the sources of threats and other men-acing factors - Олійник, Олег Вікторович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
General conclusions in the article lead to the fact that the challenge is a threatening factor and has both as historical basis and signs as modern. Such conclusions may come from the impact of past confrontations between States and coalitions of States, as well as to coproduce modern stage of civilization development. Development is associated with global processes, crisis, desire super states, coalitions of States and more developed countries to solve their own interests at the expense of the weaker countries. Within the state there is a similar model when the political parties and extremist, criminal groups decide their own interests and ambitions at the expense of other citizens of the society. The challenge is the first step in any conflict and confrontation. And it is another feature of this threatening factor on which the side initiator of the conflict makes statements about claims to the opposite side and demands in order to achieve as their local and purposes overstepping local boundaries. The following important conclusion. If the initiator side of the conflict cannot achieve its goals, activities and means on stage threatening factor, the call may escalate into full-scale implementation of threats, that is, to bring to the stage the danger. Therefore, the danger is the highest stage of negative consequences in this range. The article considers that a systematic and comprehensive approach has to provide a complete understanding of the sources of threats and threatening factors concerning the substantial entity of public policy, informational safety and security as an important component of national security. The Sources of threats should be the basis for administrative and legal definition powers and functions, regulation of relations in the sphere of this activity, the formation of organizational information security. It is necessary to understand and fix in the relevant political and legal decisions the entire spectrum of threats which are important for national security and informational security of Ukraine. The author notes that only on the basis of defined and perceived threats (risks, potential and real threats challenges and dangers) it can be possible to create a security system, resistance, to neutralize the implementation against Ukraine in different content and direction of the dangers. It is very important to be aware of state and public organizations elementary initial concepts from what and whom you should protect yourself, against whom to conduct the defense or offensive information war and implement other measures of counteraction. And it gives the possibility to determine the forces, means, activities against any threats towards Ukraine.